1981
DOI: 10.1002/hlca.19810640130
|View full text |Cite
|
Sign up to set email alerts
|

Desorption/Chemical Ionization Mass Spectrometry of Naturally Occurring Glycosides

Abstract: SummaryDesorptionlchemical ionization mass spectrometry (D/CI.-MS.) is a recently developed technique especially indicated for highly polar and non volatile compounds. Various naturally occurring glycosides such as saponins, iridoid and secoiridoid glycosides, cardenolides and flavone-0-glycosides have been investigated by this method. All the measurements were carried out on underivatized compounds. In addition to the structural informations generally furnished by field-desorption mass spectrometry (molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In early studies, derivatization was required for saponin analysis using electron impact (EI) MS [7][8][9]. The development of desorption chemical ionization mass spectrometry (DCI-MS) allowed analysis of saponins without derivatization, but only for saponins with ether glycosidic linkages [10,11]. Later, field desorption (FD) and fast atom bombardment (FAB) were also employed to analyze native saponins [12][13][14][15][16][17][18], providing information about molecular mass and sugar sequence by cleavage of glycosidic bonds.…”
mentioning
confidence: 99%
“…In early studies, derivatization was required for saponin analysis using electron impact (EI) MS [7][8][9]. The development of desorption chemical ionization mass spectrometry (DCI-MS) allowed analysis of saponins without derivatization, but only for saponins with ether glycosidic linkages [10,11]. Later, field desorption (FD) and fast atom bombardment (FAB) were also employed to analyze native saponins [12][13][14][15][16][17][18], providing information about molecular mass and sugar sequence by cleavage of glycosidic bonds.…”
mentioning
confidence: 99%
“…These inconveniences do not arise from desorption/chemical ionization mass spectroscopy (D/CI-MS) (6). We have demonstrated that this technique can be successfully used with underivatized naturally occurring glycosides such as saponins and flavonoid-Oglycosides (7,8). The present work reports on the application of D/CI-MS to some of the most important bitter principles which have been isolated in the course of our systematic investigation of Gentiana species.…”
mentioning
confidence: 99%
“…Some underivatized iridoids and secoiridoids (77) have been investigated by this technique with ammonia as a reagent gas. The quasimolecular ion (M + NH,)+ forms the base peak.…”
Section: A Chemical Ionizationmentioning
confidence: 99%